2016
DOI: 10.2967/jnumed.115.167437
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Quantification of Myocardial 11C-Meta-Hydroxyephedrine Kinetics

Abstract: 11 C-meta-hydroxyephedrine ( 11 C-HED) kinetics in the myocardium can be quantified using a single-tissue-compartment model together with a metabolite-corrected arterial blood sampler input function (BSIF). The need for arterial blood sampling, however, limits clinical applicability. The purpose of this study was to investigate the feasibility of replacing arterial sampling with imaging-derived input function (IDIF) and venous blood samples. Methods: Twenty patients underwent 60-min dynamic 11 C-HED PET/CT sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 17 publications
(36 reference statements)
0
4
0
Order By: Relevance
“…In humans, [ 11 C]mHED uptake is stronger affected by myocardial blood flow than in mice (under isoflurane anaesthesia), as the mean human resting myocardial blood flow is ~ 1 ml/min/g [ 29 ] (0.5–0.6 ml/min/g plasma flow), while K 1 of [ 11 C]mHED uptake was up to 0.6 ml/min/g in a recent PET study [ 30 ]. Patients with ongoing ischemia may display regionally reduced [ 11 C]mHED uptake due to significant perfusion defects [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…In humans, [ 11 C]mHED uptake is stronger affected by myocardial blood flow than in mice (under isoflurane anaesthesia), as the mean human resting myocardial blood flow is ~ 1 ml/min/g [ 29 ] (0.5–0.6 ml/min/g plasma flow), while K 1 of [ 11 C]mHED uptake was up to 0.6 ml/min/g in a recent PET study [ 30 ]. Patients with ongoing ischemia may display regionally reduced [ 11 C]mHED uptake due to significant perfusion defects [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ratios of plasma/whole blood concentrations and parent fractions derived from the manual blood samples were fitted to a sigmoid function after a venous-to-arterial blood transformation was applied. 19 Subsequently, the arterial whole blood TAC was multiplied by both the fitted plasma/whole blood ratio and parent fraction curves to obtain the metabolite corrected arterial plasma TAC. Next, segmental VOIs were defined manually in all short axis images of the final frame of the dynamic scan.…”
Section: Methodsmentioning
confidence: 99%
“…In the literature, other parameters have been assessed using HED PET such as the global LV mean retention index and volumes of distribution. [15,25] These have been shown to be more susceptible to variation than the regional denervation scores, using either the retention index model or the distribution volume model. [15] These studies have concluded that the largest sources of variation were factors related to test-retest variability, rather than variability between observers.…”
Section: Comparison To the Current Literaturementioning
confidence: 99%